The pursuit of beauty by an aesthete: A study of Harold Acton’s manuscripts of Popular Chinese Plays - Guan, Xingzhong (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
This article examines Harold Acton’s translation of Popular Chinese Plays. It examines the modifications Acton made in the final polishing stage of his translation and explores possible linguistic, aesthetic and social considerations for such alterations. Four plays—Ch’un-hsiang Nao Hsueh ????, Yü Chou Fêng???, Lin Ch’ung Yeh Pên????, and Shih Hou Chi???—were selected for this research. Computerized data were analysed using Wordsmith 4.0. This article demonstrates that at this later stage of the translation’s genesis, Acton gives priority to the overall effectiveness and coherence of the translation while paying less attention to lexical and syntactical details. His corrections to the manuscript indicate that the translator departs from the source text, displaying more independence as a writer. The purpose of this analysis is to show how translators’ strategies can evolve during the genesis of a translation, thus complicating the common assumption that translators adopt a consistent “stance” when translating.